2022
DOI: 10.1038/s41598-022-20379-1
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression and anxiety increased marginally from before to during the COVID-19 pandemic among young adults in Canada

Abstract: We documented changes in depressive and anxiety symptoms from before to during the COVID-19 pandemic among young adults and investigated whether changes differed across participant characteristics. Data were available in an investigation of 1294 grade 7 students recruited in 1999–2000. For this analysis, we used data collected pre-pandemically in 2017–20 (mean (SD) age = 30.6 (1.0)) and during the pandemic in 2020–21 (mean (SD) age = 33.6 (0.6)). 673 participants with data in both cycles were retained for anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…In Chinese population the prevalence of depression, anxiety, sleep disorders, and posttraumatic stress symptoms was shown to be moderately high during COVID-19 crisis (21, 36-39), as it was among citizens in South Korea, India, Italy, and Denmark, where the authors showed similar results in their articles (40-43). However, Bélanger et al (44) in Canada pointed out completely opposite findings, in contrast to their Canadian colleagues who confirm similar observations as in the previously mentioned countries (45). Interestingly, when it comes to comparison between US and China, according to Wang et al (46), Americans reported more stress and depressive symptoms, while Chinese reported higher acute-traumatic stress symptoms.…”
Section: Discussionmentioning
confidence: 76%
“…In Chinese population the prevalence of depression, anxiety, sleep disorders, and posttraumatic stress symptoms was shown to be moderately high during COVID-19 crisis (21, 36-39), as it was among citizens in South Korea, India, Italy, and Denmark, where the authors showed similar results in their articles (40-43). However, Bélanger et al (44) in Canada pointed out completely opposite findings, in contrast to their Canadian colleagues who confirm similar observations as in the previously mentioned countries (45). Interestingly, when it comes to comparison between US and China, according to Wang et al (46), Americans reported more stress and depressive symptoms, while Chinese reported higher acute-traumatic stress symptoms.…”
Section: Discussionmentioning
confidence: 76%
“…A survey by Statistics Canada reported that 46,000 Canadians reported poorer mental health since the onset of social distancing, and that 88% had experienced at least one symptom of anxiety during the COVID-19 pandemic in 2020 [ 9 ]. Research conducted by Sylvestre et al found that symptoms of anxiety increased significantly among Canadian young adults during the COVID-19 pandemic [ 10 ].…”
Section: Introductionmentioning
confidence: 99%